2023
DOI: 10.22270/jddt.v13i4.5793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exposure to Soot on Activities of Alanine Transaminase, Gamma Glutamyl Transferase and Lipase among Cooks in Nnewi

Abstract: Exposure to soot can lead to hepatic and pancreatic dysfunction. This study determined serum alanine transaminase (ALT), gamma-glutamyl transferase (GGT), and triacylglycerol lipase activities of cooks exposed to soot. Thirty (30) participants (cooks) were exposed to soot (test group), and thirty (30) participants not exposed to soot (control group) were recruited. Ethical approval was obtained from the Ethics committee of the Faculty of Health Sciences and Technology, Nnamdi Azikiwe University, and informed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This research observed no association between the levels of Interleukin 4, High sensitivity C-reactive protein, and activity of alanine transaminase and the body mass index, systolic blood pressure, and diastolic blood pressure of cooks exposed to soot. This agrees with the work of 34 on the effect of exposure to soot on the activities of liver enzymes, which observed no relationship between the activity of alanine transaminase and the BMI, systolic blood pressure, and diastolic blood pressure. No statistically significant correlation was seen between BMI and interleukin 4 (IL-4) 45 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This research observed no association between the levels of Interleukin 4, High sensitivity C-reactive protein, and activity of alanine transaminase and the body mass index, systolic blood pressure, and diastolic blood pressure of cooks exposed to soot. This agrees with the work of 34 on the effect of exposure to soot on the activities of liver enzymes, which observed no relationship between the activity of alanine transaminase and the BMI, systolic blood pressure, and diastolic blood pressure. No statistically significant correlation was seen between BMI and interleukin 4 (IL-4) 45 .…”
Section: Discussionsupporting
confidence: 92%
“…This result differs from the findings of 42 where there was a significantly higher difference in the mean serum activity of ALT in participants exposed to air pollution in areas near oil drilling sites since birth compared with control. In a study to determine the serum activities of liver enzymes in cooks exposed to soot, 34 found the serum activity of alanine transaminase to be significantly higher in the test group compared control. Additionally, 43 in a Taiwanese population study saw an association between long-term exposure to particulate matter and an increase in the activities of liver enzymes, including alanine transaminase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation